Value Proposition and Human Capital: strategic marketing practices - Scharf, Edson Roberto (Review of Business Management, 2012)
One of the marketing practices adopted by organizations to be more efficient in face of the excess of advertising is the value proposition to consumers. The adoption of human capital is one of the options. To such end, the aim of this study was to confirm the use of the ‘human capital’ construct in both the conceptualization and development of the value proposition stages. The social group was comprised of marketing executives working for companies regarded as the best companies to work for. The results of the exploratory procedure showed that all companies understand that human capital is a key attribute in order to develop value proposition and that brand value takes place having human capital as one of its main pillars. The results of the descriptive procedure confirmed the human capital as one of the concepts for value proposition, although such conceptualization process is often changed by strategic partners in the development stage. Key words: Value proposition. Brand identity. Branding. Human capital.